2013
DOI: 10.1186/1471-2334-13-605
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of serological failure after treatment in HIV-infected patients with early syphilis in the emerging Era of universal antiretroviral therapy use

Abstract: BackgroundThe optimal treatment of early syphilis (primary, secondary and early latent) in HIV-infected patients remains controversial. The Center for Diseases Control STD Treatment Guidelines recommended 1 dose of benzathine penicillin G (BPG) regardless of HIV infection. However, many providers modify the treatment for early syphilis.MethodsWe performed a retrospective chart review of all cases of early syphilis with positive serologic test results in HIV-infected patients from May 2006 to May 2011 in 2 larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 19 publications
10
35
1
6
Order By: Relevance
“…Treatment failure was observed in 12% of episodes that were included in the study, which is a proportion that is similar to what has been observed in other studies regarding uninfected individuals [11] and PLWH in the post-ART era [9, 10]. …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Treatment failure was observed in 12% of episodes that were included in the study, which is a proportion that is similar to what has been observed in other studies regarding uninfected individuals [11] and PLWH in the post-ART era [9, 10]. …”
Section: Discussionsupporting
confidence: 84%
“…Immunosuppression has been associated with treatment failure in syphilis, as reported in previous studies on PLWH [10, 22] and subjects with an impaired immune system have been reported to respond more slowly to syphilis treatment, compared with those with a good immunological status [10, 24]. In this study, higher RPR titers were associated with treatment response both in early and late syphilis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[22] In contrast, other studies suggest that ART has no influence on syphilis incidence, [23,24] or even increases it, [25–27] while others suggest no effect of ART on treatment or serological failure. [28,29] …”
Section: Introductionmentioning
confidence: 99%
“…Más utánvizsgá-lók nem találtak kevesebb kezelési elégtelenséget, mintha nagyobb dózisban adták volna a penicillint, de felhívják a fi gyelmet, hogy ha az RPR kezdeti titere <1:16, és/vagy a CD4+ T-lymphocyta-szám <350 sejt/ μl, gondos monitorozás szükséges szerológiai rezisztencia irányában [46]. 2007 előtt syphilisszel kezelt HIVpozitív neurosyphilises betegek ellenőrző vizsgálata évekkel később mind a klinikai vizsgálat, mind a liquor cerebrospinalis vizsgálat tekintetében negatív volt (34/35 esetben) [47].…”
Section: Hiv/syphilis Koinfekcióunclassified